2006
DOI: 10.1158/1535-7163.mct-06-0394
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative action of tamoxifen and c-Src inhibition in preventing the growth of estrogen receptor–positive human breast cancer cells

Abstract: It has long been appreciated that estrogenic signaling contributes to breast cancer progression. c-Src is also required for a number of processes involved in tumor progression and metastasis. We have previously identified the K303R mutant estrogen receptor A (ERA) that confers hypersensitivity to low levels of estrogen. Because ERA and c-Src have been shown to interact in a number of different systems, we wanted to evaluate the role of c-Src kinase in estrogen-stimulated growth and survival of ERA-positive bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 34 publications
3
41
0
Order By: Relevance
“…DCR was 53% for all evaluable patients and median PFS was 13 weeks, which was similar to the median PFS reported for capecitabine monotherapy in other studies (36,37). However, in post hoc subset analysis of patients with HRþ tumors, DCR was 78% and median PFS was 23.1 weeks; the suggestion of enhanced activity against HRþ tumors and bone metastases may be related to the role of Src kinase in HR signaling (14)(15)(16)(17) and inhibition by dasatinib on osteoclasts and on tumor resident in bone (9,26). Dasatinib has been studied in ABC in combination with paclitaxel (38) or with ixabepilone (39) and in combination with hormonal therapies for ERþ disease, including fulvestrant (40), exemestane (41), and letrozole (in progress, NCT00696072).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…DCR was 53% for all evaluable patients and median PFS was 13 weeks, which was similar to the median PFS reported for capecitabine monotherapy in other studies (36,37). However, in post hoc subset analysis of patients with HRþ tumors, DCR was 78% and median PFS was 23.1 weeks; the suggestion of enhanced activity against HRþ tumors and bone metastases may be related to the role of Src kinase in HR signaling (14)(15)(16)(17) and inhibition by dasatinib on osteoclasts and on tumor resident in bone (9,26). Dasatinib has been studied in ABC in combination with paclitaxel (38) or with ixabepilone (39) and in combination with hormonal therapies for ERþ disease, including fulvestrant (40), exemestane (41), and letrozole (in progress, NCT00696072).…”
Section: Discussionsupporting
confidence: 82%
“…12) and Her2/neu (13) and via the estrogen receptor (ER; refs. 14, 15) and contribute to endocrine therapy resistance (16,17) as well as resistance to Her2 inhibition (18). Src kinase activity also plays a role in VEGF-induced angiogenesis and vascular permeability (19), VEGF production (20), and downstream VEGF signaling (21).…”
Section: Introductionmentioning
confidence: 99%
“…One setting of interest is treatment of patients with endocrine-resistant breast cancer. Multiple in vitro observations have shown increased SRC expression and activity in ERþ cell lines exposed to estrogen (26) and in those with tamoxifen resistance (27). Recent preclinical studies have shown a role for activated SRC in ER degradation, suggesting a potential mechanism in development of endocrine resistance (28).…”
Section: Discussionmentioning
confidence: 99%
“…Recent preclinical studies have shown a role for activated SRC in ER degradation, suggesting a potential mechanism in development of endocrine resistance (28). Preclinical studies combining SRC inhibitors with antiestrogens have shown synergistic antitumor activity (26,29,30). Trials of dasatinib combined with endocrine therapy in patients with HRþ MBC are underway using a better-tolerated once daily schedule of dasatinib.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ability to inhibit Src activity, alongside targeting of the ER with anti-oestrogens, may enhance the anti-tumour activity seen with each agent alone. Indeed, two recent studies provide compelling evidence to support such a hypothesis, demonstrating the short-term effectiveness of such combinational treatments in preventing the growth of MCF7 cells [25,44]. However, it is currently unknown whether co-targeting both Src and the ER is effective in other ERpositive cell lines and whether such treatment regimens would be effective in circumventing the phenomena of acquired tamoxifen resistance that occurs following chronic exposure to this agent [8,45,46].…”
Section: Discussionmentioning
confidence: 99%